Strategi Komunikasi (MSS) Masyrakat Sehat Sriwijaya Banyuasin Dalam Menyebarkan Program Eliminasi TBC Kepada Masyarakat - M. Rapli juliansyah; Sumaina Duku; Hamidah Hamidah (CV. ITTC INDONESIA, 2023)
The purpose of this study was to determine the communication strategy of the Banyuasin MSS (Masyrakat Sehat Sriwijaya) in disseminating TB elimination programs to the community. The research was conducted because today many people are less concerned about health, concern for managing a healthy lifestyle for some people is still very minimal in developing countries like Indonesia. Health problems in Indonesia are endlessly discussed, especially for people who have incomes below the average. Therefore researchers are interested in conducting research in this field. This study uses a qualitative descriptive research method. the researcher wants to describe the conditions that will be observed in the field in a more specific, transparent, and in-depth manner. This study attempts to describe situations/events so that the data that will be collected is descriptive in nature to identify the internal and external environment in MSS (Masyarakat Sehat Sriwijaya) Banyuasin.